Performance of the Electrical Energy Index in the Light of Institutional Changes in the Brazilian Electricity Sector - Costa, Caio Corrêa; Leite, André Luís da Silva; De Castro, Nivalde José (International Journal of Energy Economics and Policy, 2018)
This study aims to analyze the performance of the Electrical Energy Index in the perspective of Institutional Changes in Brazilian Electricity Sector. The research focused its efforts in analyze the impact of Provisional Measure No. 579 of September 11, 2012 (converted into Law No. 12783 / 2013) on the stocks of the Electric Power Sector, represented here by the respective sector index in BM&FBOVESPA. The research results reveal that from the release of Provisional Measure No. 579 by the end of the observed time interval (April 2015), the Electrical Energy Index didn’t recovered from the reversal trend caused by this measure, which once was a growth trend but instantly became a stagnation / decay trend. Keywords: Brazilian Electricity Sector. Capital Markets. Electrical Energy Index. Laws and Regulations. Provisional Measure No. 579/2012. JEL Classifications: G38; K23; L51; Q40; Q48.